Self-medication in Brazil: Prevalence, risks and implications for public health — an integrative review (Research, Society and Development, 2026)
Self-medication is defined as the use of medications without prescription or guidance from qualified health professionals and is deeply rooted in Brazilian culture. This study aimed to analyze the prevalence of self- medication within the national context by identifying key determining factors and associated public health risks. An integrative literature review was conducted using the SciELO, PubMed, and Virtual Health Library (VHL) databases for publications between 2015 and 2025. The findings reveal significant prevalence rates that vary by region and population group, particularly highlighting the indiscriminate use of analgesics and anti- inflammatories. Identified main risks include poisoning, adverse drug interactions, and worsening bacterial resistance. It is concluded that self-medication in Brazil represents a multifactorial phenomenon requiring strengthened policies for rational drug use and enhanced pharmaceutical care as harm mitigation strategies.